1982
DOI: 10.1037/0012-1649.18.4.571
|View full text |Cite
|
Sign up to set email alerts
|

A multimethod comparison of popular and unpopular children.

Abstract: Children who have peer relationship problems have numerous adjustment difficulties in later life. This study compared popular and unpopular children in a multimethod comparison procedure to identify differences between these two populations. Children were identified as being in popular and unpopular groups by two sociometric instruments. Subsequently, differences between the two groups were assessed by teacher reports, classroom observations, an achievement test, and ratings on role-play situations. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
4

Year Published

1983
1983
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 7 publications
3
36
0
4
Order By: Relevance
“…Most research focusing on social competence of children has examined behavioral differences among children who vary on their sociometric status (e.g., Vosk et al, 1982). The identification of differences in social perception abilities indicates that simply teaching socially deficit children appropriate behavior will not be sufficient (Morrison and Bellack, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Most research focusing on social competence of children has examined behavioral differences among children who vary on their sociometric status (e.g., Vosk et al, 1982). The identification of differences in social perception abilities indicates that simply teaching socially deficit children appropriate behavior will not be sufficient (Morrison and Bellack, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown that as compared to children low on peer popularity, popular children show less variability across different adjustment domains. As a group, these children have been found to be less diverse in their ratings on measures of teacherrated and self-rated depression, conduct problems, and negative interactions with peers (Vosk, Forehand, Parker, & Rickard, 1982). Thus, it is possible that resilient teenagers do, in fact, show relatively high stability across adjustment domains and that the low interdomain correlations previously achieved with overall samples arise from high variability among the "average" or nonresilient children.…”
mentioning
confidence: 94%
“…Children who lack important social skills often are rejected by their peers, have trouble interacting with their teachers and families, and have emotional diffi culties (Coie & Dodge, 1988;Dodge, 1983;Parker & Asher, 1987;Vosk, Forehand, Parker, & Rickard, 1982). Furthermore, social skills defi cits are frequently associated with children exhibiting externalizing disorders such as delinquency and conduct disorder, as well as those with internalizing disorders like depression and anxiety (Mash & Barkley, 1996).…”
mentioning
confidence: 99%